Peran Regulasi Modern dalam Menjaga Integritas Sistem Hukum Perbankan Digital - Aqila Acyuta Endrosava; Suwarsit Afiliasi (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2024)
Advances in digital technology have brought profound changes to the banking industry, providing significant benefits while raising complex legal challenges. This research aims to evaluate the role of current regulations in addressing the various legal challenges that have emerged in the digital era, including issues of data security, consumer protection, and financial transaction integrity. Key challenges identified include cyber threats, privacy breaches, digital fraud, as well as regulatory incompatibilities across jurisdictions. Using a descriptive and qualitative approach, this research utilizes data from various sources, such as banking regulations, research reports, case studies, and best practices released by relevant authorities. The analysis aims to uncover the weaknesses of existing regulations and propose solutions that can improve regulatory effectiveness. The results of this research are expected to support the development of more resilient regulations in the digital era and provide guidance for banking practitioners, supervisors, and legal researchers in addressing various legal challenges in the banking sector.